Reading Beauty - Underwood, Deborah (Chronicle Books LLC, 2019)
In this version of Sleeping Beauty, told in verse, the Princess is threatened with a curse which will start with a paper cut; devastated that all her books have been taken away, she sets out with her dog, Prince, to find the fairy who cast the curse and make her reverse it.